Observation of the $${{{\Lambda }} _{\text {b}}^{{0}}} \rightarrow {{\text {J}/\uppsi }} {{{\Xi }} ^{{-}}} {{\text {K}} ^{{+}}} $$ Λ b 0 → J / ψ Ξ - K + decay - CMS Collaboration; A. Hayrapetyan; A. Tumasyan; W. Adam; J. W. Andrejkovic; T. Bergauer; S. Chatterjee; K. Damanakis; M. Dragicevic; A. Escalante Del Valle; P. S. Hussain; M. Jeitler; et al. (European Physical Journal C: Particles and Fields)
Abstract Using proton–proton collision data corresponding to an integrated luminosity of $$140\hbox { fb}^{-1}$$ 140 fb - 1 collected by the CMS experiment at $$\sqrt{s}= 13\,\text {Te}\hspace{-.08em}\text {V} $$ s = 13 Te V , the $${{{\Lambda }} _{\text {b}}^{{0}}} \rightarrow {{\text {J}/\uppsi }} {{{\Xi }} ^{{-}}} {{\text {K}} ^{{+}}} $$ Λ b 0 → J / ψ Ξ - K + decay is observed for the first time, with a statistical significance exceeding 5 standard deviations. The relative branching fraction, with respect to the $${{{\Lambda }} _{\text {b}}^{{0}}} \rightarrow {{{\uppsi }} ({2\textrm{S}})} {{\Lambda }} $$ Λ b 0 → ψ ( 2 S ) Λ decay, is measured to be $$\mathcal {B}({{{\Lambda }} _{\text {b}}^{{0}}} \rightarrow {{\text {J}/\uppsi }} {{{\Xi }} ^{{-}}} {{\text {K}} ^{{+}}} )/\mathcal {B}({{{\Lambda }} _{\text {b}}^{{0}}} \rightarrow {{{\uppsi }} ({2\textrm{S}})} {{\Lambda }} ) = [3.38\pm 1.02\pm 0.61\pm 0.03]\%$$ B ( Λ b 0 → J / ψ Ξ - K + ) / B ( Λ b 0 → ψ ( 2 S ) Λ ) = [ 3.38 ± 1.02 ± 0.61 ± 0.03 ] % , where the first uncertainty is statistical, the second is systematic, and the third is related to the uncertainties in $$\mathcal {B}({{{\uppsi }} ({2\textrm{S}})} \rightarrow {{\text {J}/\uppsi }} {{{\uppi }} ^{{+}}} {{{\uppi }} ^{{-}}} )$$ B ( ψ ( 2 S ) → J / ψ π + π - ) and $$\mathcal {B}({{{\Xi }} ^{{-}}} \rightarrow {{\Lambda }} {{{\uppi }} ^{{-}}} )$$ B ( Ξ - → Λ π - ) .